Advances in solid state physics - Queisser, Hans-Joachim (Festkopper probleme, 1973)
Festkorper Probleme XIII: Advances in Solid State Physics is a collection of papers from plenary lectures of the solid states division of the German Physical Society in Munster, on March 19-24, 1973. This collection deals with semiconductor physics, surface phenomena, and surface physics. One paper reviews the findings on experiments on the magnetic, optical, electrical, and structural properties of layer type crystals, particularly metal dichalcogenides. This book then discusses the van der Waals attraction using semi-classical methods to explain the correlation in different atoms. This disc.